PERCOBAAN PEMUTIHAN KULIT ROTAN SEGA (CALAMUS CAESIUS BL.) DENGAN METODA PERENDAMAN DALAM LARUTAN HIDROGEN PEROKSIDA (H2°2) - Abdul Hakim Lukman (Pusat Penelitian dan Pengembangan Hasil Hutan, 1992)
The effects of bleaching of sega rattan (Calamus caesius Bl) peel by soaking in the hydrogen peroxyde of several concentration levels (1 , 3, 5, and 7 percent) and soaking times ( 1, 3, and 5 hours) on rattan peel quality were studied at the Forest Products Research and Development Centre Laboratory in Bogor. Results showed that the unblea- ched rattan peel has the brightness of 38.8 percent and the tensile strength parallel to grain of 412.09 kg/cm2 while for the bleached ones, those figures are 44. 74 percent and 374.99 kg/cm2, respectively.It is found that bleaching agent concenlration has a highly significant effect on both brightness and tensile strength parallel to grain. The brightness (Y) was significantly improved with the increasing of bleaching agent concentrations (X) which can be expressed by the regression equation of Y = 40.2365 + 1.1265 X (r = 0.9992). On the other hand, tensile strength (Y) was significantly decreased with the increasing of hydrogen peroxyde concentrations (X, as expressed by the following rearession equation: Y = 421.37 5 - 11.675 x (r = 0.9888 ).The apllcation of 5 percent hydrogen peroxyde concentration is optimum which could improve the brightness up to 46. 03 percent, and reduced the tensile strength down to 364.8 kg/cm2.